IMPLEMENTASI SISTEM PAKAR PADA PENYAKIT BUAH PEPAYA CALIFORNIA BERBASIS ANDROID MENGGUNAKAN METODE FORWARD CHAINING - Irwan Adi Pribadi; Titik Nur Aeny; Akmal Junaidi; Tio Arisandi (Jurnal Pepadun, 2022)
California papaya is one of the varieties of papaya developed by the Bogor Agricultural Institute known as IPB-9. California papaya is widely cultivated by farmers in Indonesia because it is quite profitable, but this plant is not immune from disease. For this reason, farmers must understand the aspects of california papaya disease so that their hard work from california papaya farming brings satisfactory results. With the advancement of science and information technology today, farmers can find out information about california papaya disease and how to control it easily. This research produces an expert system application that can find out information about california papaya disease by using the forward chaining method. Farmers can use various features in this california papaya application. The first feature is disease diagnosis. In this feature, farmers will choose the symptoms that have been provided by the application, totaling 28 symptoms which will then be drawn conclusions in the form of results and ways to overcome the disease concluded. The second feature, the application provides a list of 9 diseases in california papaya so that farmers can find out in full about the disease and how to overcome it.